Prognostic value of somatic focal amplifications on chromosome 30 in canine oral melanoma. (13th September 2019) - Prouteau, Anais; Chocteau, Florian; de Brito, Clotilde; Cadieu, Edouard; Primot, Aline; Botherel, Nadine; Degorce, Frédérique; Cornevin, Laurence; Lagadic, Marie A.; Cabillic, Florian; de Fornel‐Thibaud, Pauline; Devauchelle, Patrick; et al.
Abstract: Canine oral melanoma is the first malignancy of the oral cavity in dogs and is characterized by a local invasiveness and a high metastatic propensity. A better knowledge of genetic alterations is expected to improve management of this tumour. Copy number alterations are known characteristics of mucosal melanomas both in dogs and humans. The goal of this study was to explore the prognostic value of somatic focal amplifications on chromosomes ( Canis Familiaris [CFA]) 10 and 30 in canine oral melanoma. The cohort included 73 dogs with oral melanoma confirmed by histology, removed surgically without adjuvant therapy and with a minimal follow‐up of 6 months. Epidemiological, clinical and histological data were collected and quantitative‐PCR were performed on formalin‐fixed paraffin‐embedded (FFPE) samples to identify specific focal amplifications. The 73 dogs included in the study had a median survival time of 220 days. Focal amplifications on CFA 10 and 30 were recurrent (49.3% and 50.7% of cases, respectively) and CFA 30 amplification was significantly associated with the amelanotic phenotype ( P = .046) and high mitotic index (MI; P = .0039). CFA 30 amplification was also linked to poor prognosis ( P = .0005). Other negative prognostic factors included gingiva location ( P = .003), lymphadenomegaly ( P = .026), tumour ulceration at diagnosis ( P = .003), MI superior to 6 mitoses over 10 fields ( P = .001) and amelanotic tumour ( P = .029). In multivariate analyses using Cox proportional hazards regression, CFA 30 amplification (Hazard ratio [HR] = 2.08; P = .011), tumour location (HR = 2.20; P = .005) and histological pigmentation (HR = 1.87; P = .036) were significantly associated with shorter survival time. Focal amplification of CFA 30 is linked to an aggressive subset and constitutes a new prognostic factor.